Survey Methods for Estimating the Size of Weak-Tie Personal Networks. Issue 2 (August 2022) - Feehan, Dennis M.; Hai Son, Vo; Abdul-Quader, Abu
Researchers increasingly use aggregate relational data to learn about the size and distribution of survey respondents' weak-tie personal networks. Aggregate relational data are collected by asking questions about respondents' connectedness to many different groups (e.g., "How many teachers do you know?"). This approach can be powerful, but to use aggregate relational data, researchers must locate external information about the size of each group from a census or administrative records (e.g., the number of teachers in the population). This need for external information makes aggregate relational data difficult or impossible to collect in many settings. Here, the authors show that relatively simple modifications can overcome this need for external data, significantly increasing the flexibility of the method and weakening key assumptions required by the associated estimators. The key idea is to estimate the size of these groups from the sample of survey respondents, rather than relying on external sources of information. These methods are appropriate for using a sample survey to study the size and distribution of weak-tie network connections. They can also be used as part of the network scale-up method to estimate the size of hidden populations. The authors illustrate this approach with two empirical studies: a large simulation study and original household survey data collected in Hanoi, Vietnam.